2022
DOI: 10.1038/s41598-022-23840-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the level of perceived social support among community-dwelling stroke survivors using the Multidimensional Scale of Perceived Social Support

Abstract: Social support has an important role in stroke rehabilitation. The Multidimensional Scale of Perceived Social Support (MSPSS) is an instrument examining the adequacy of perceived social support. However, the psychometric properties of the Chinese version of MSPSS (MSPSS-C) have not been examined in Chinese people with stroke. This study aimed at investigating the psychometric properties of the MSPSS-C, identifying the correlations between MSPSS-C scores and health-related measures of these people; and examinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The PSQI, a widely utilized tool for evaluating sleep quality, serves as a reliable indicator capable of reflecting the global sleep status across diverse populations, with a Cronbach's α ranging from 0.82 to 0.83, and higher global PSQI scores indicate poorer sleep quality (Huang and Zhu 2020). The MSPSS, a prominent instrument for assessing social support, assesses the perceived adequacy of social support, with higher scores indicating greater perceived social support (Ng et al 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PSQI, a widely utilized tool for evaluating sleep quality, serves as a reliable indicator capable of reflecting the global sleep status across diverse populations, with a Cronbach's α ranging from 0.82 to 0.83, and higher global PSQI scores indicate poorer sleep quality (Huang and Zhu 2020). The MSPSS, a prominent instrument for assessing social support, assesses the perceived adequacy of social support, with higher scores indicating greater perceived social support (Ng et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The MSPSS, a prominent instrument for assessing social support, assesses the perceived adequacy of social support, with higher scores indicating greater perceived social support (Ng et al. 2022). The instrument demonstrates a high level of internal consistency, with a Cronbach's α of 0.89 (Ng et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores indicate a greater perceived level of support. The Chinese version of the MSPSS has been validated and shown to be reliable [ 35 ]. In our study, Cronbach’s alpha coefficient for internal consistency was calculated to be 0.86.…”
Section: Methodsmentioning
confidence: 99%
“…Higher total scores on this scale indicate higher levels of perceived social support among participants. The Chinese version of the MSPSS, translated by Jiang et al ( 36 ), demonstrated satisfactory reliability and validity and has been widely employed in diverse studies ( 37 , 38 ). In the present study, the Cronbach’s α of the scale was 0.971.…”
Section: Methodsmentioning
confidence: 99%